Mengkaji Efektivitas Kebijakan Pendidikan Inklusif: Potret Persepsi Masyarakat - subhan subhan; Pertiwi Kamariah Hasis (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2025)
Inclusive education policies have been widely adopted globally, yet significant gaps persist between policy intentions and implementation realities. This study scrutinizes the effectiveness of inclusive education policy through community perception, examining stakeholder attitudes, experiences, and barriers to successful implementation. A mixed-methods convergent parallel design was employed, combining qualitative phenomenological interviews and focus group discussions with key stakeholders (n=65) and a quantitative cross-sectional survey of community members (n=750). Participants included educators, parents, policy makers, community leaders, and students across urban and rural settings. Qualitative data were analyzed using thematic analysis, while quantitative data employed descriptive and inferential statistics including ANOVA and regression analysis. Findings reveal significant variations in community perceptions based on stakeholder roles, geographic location, and previous exposure to inclusive education. Key barriers identified include inadequate teacher training, insufficient resources, cultural stigma, and limited community awareness of inclusive education principles. However, positive attitudes emerged among stakeholders with direct inclusive education experience, highlighting the importance of exposure in shaping perceptions. The study demonstrates that policy effectiveness is critically dependent on community understanding, acceptance, and active participation in implementation processes. Results provide valuable insights for policy makers to develop community-responsive inclusive education strategies and targeted interventions to enhance stakeholder engagement and support.